Peran Perempuan Minangkabau sebagai Aktualisasi Diri dalam Novel Perempuan Batih dan Novel Limpapeh Karya A. R. Rizal: Perspektif Naomi Wolf: The Role of Minangkabau Women as Self-Actualization in the Novel Perempuan Batih and the Novel Limpapeh by A. R. Rizal: Naomi Wolf's Perspective - Harini, Konti; Rengganis, Ririe; Indarti, Titik (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study examines Minangkabau culture, which adheres to a matrilineal kinship system, in which women, particularly mothers and wives, are seen as guardians of family honor and stability. This system is often considered a form of superiority in the social structure, but it does not necessarily guarantee the fulfillment of women's rights as free and independent human beings. This study aims to describe in depth the roles, struggles, and self-actualization processes of Minangkabau women facing restrictive cultural norms and relates them to Naomi Wolf's liberal feminist theory. Using a qualitative descriptive approach, this study analyzes two novels by A. R. Rizal, Perempuan Batih (Women of the Batih) and Limpapeh (Limpapeh), as the primary data sources. In both literary works, female characters are depicted as more dominant in the domestic sphere as mothers and children, yet they carry a significant moral and social burden. They face challenges articulating their thoughts, choices, and aspirations in the public sphere, which tends to be limited by customary values. From Naomi Wolf's perspective, the struggles of Minangkabau women in these novels reflect an effort to liberate themselves from restrictive social constructs. These struggles include seeking education, making personal decisions, and having the courage to voice one's identity and will. This research concludes that while the matrilineal system provides symbolic space for women, inequality in the distribution of power and rights persists. Therefore, critical reflection and cultural transformation are crucial to building substantial gender equality within Minangkabau society.